PIC Microcontrollers : An Introduction to Microelectronics - Bates, Martin, 1952-; Bates, Martin, 1952- (Amsterdam ; London : Elsevier/Newnes, 2004)
The PIC chip encompasses most of the technology microelectronics students need to know about in order to understand computer and microprocessor systems. This text will enable readers to start using this chip for their own projects and designs.
Revision of: Introduction to microelectronic systems : the PIC 16F84 microcontroller. London : Arnold, 2000.
Includes index.
Keywords: Programmable controllers; Microprocessors -- Programming